2000
DOI: 10.1046/j.1365-2559.2000.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Helicobacter pylori‐dependent gastritis with gastric carcinomas in young Japanese patients: histopathological comparison of diffuse and intestinal type cancer cases

Abstract: As well as the high prevalence of H. pylori in young subjects with gastric cancer, it is clear that persistent infection induces mucosal damage, resulting in atrophy and intestinal metaplasia. Thus, acute/chronic gastritis could play an essential role in the early development of neoplasia in the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 28 publications
1
23
1
4
Order By: Relevance
“…With regard to glandular atrophy and intestinal metaplasia of the background mucosa, our young patients were mostly infected by H. pylori, however, they had less degree of corporal glandular atrophy and less frequent intestinal metaplasia around the intramucosal gastric cancer than elderly patients did. This result is consistent with that of the previous report by Mori et al 2 On the other hand, Koshida et al 18 reported that there was significantly higher prevalence of H. pylori infection, glandular atrophy and intestinal metaplasia in cases with gastric cancer than in cases without gastric cancer in young patients. This result is not consistent with the above ones including ours, however, Koshida et al 18 treated with patients younger than 40 years old (total of 40 patients, including only nine patients under 30 years of age).…”
Section: Intramucosal Gastric Cancer In the Youngsupporting
confidence: 93%
See 3 more Smart Citations
“…With regard to glandular atrophy and intestinal metaplasia of the background mucosa, our young patients were mostly infected by H. pylori, however, they had less degree of corporal glandular atrophy and less frequent intestinal metaplasia around the intramucosal gastric cancer than elderly patients did. This result is consistent with that of the previous report by Mori et al 2 On the other hand, Koshida et al 18 reported that there was significantly higher prevalence of H. pylori infection, glandular atrophy and intestinal metaplasia in cases with gastric cancer than in cases without gastric cancer in young patients. This result is not consistent with the above ones including ours, however, Koshida et al 18 treated with patients younger than 40 years old (total of 40 patients, including only nine patients under 30 years of age).…”
Section: Intramucosal Gastric Cancer In the Youngsupporting
confidence: 93%
“…Our patients under 30 years old were much younger than those of other reports, which dealt the age of under 40 [9][10][11][12]15,18 or 35 13,14 years as the young group. Therefore, our present materials are considered to be more suitable for analysis of carcinogenesis of cancer in young patients.…”
Section: Intramucosal Gastric Cancer In the Youngcontrasting
confidence: 55%
See 2 more Smart Citations
“…Longterm infection with H. pylori has been reported to result in H. pylori-associated chronic atrophic gastritis, which has been shown to correlate closely with gastric cancer, especially in young adults [16][17][18][19]. The endoscopic characteristics of H. pylori-associated gastritis in young adults have revealed nodular, rugal hyperplastic, and chronic atrophic gastritis to be specifi c to patients with H. pylori infection [20].…”
Section: Introductionmentioning
confidence: 99%